Southwest Florida Plant Diagnostic Clinic - Pamela Roberts; Shea Teems; Ramdas Kanissery; Katherine Hendricks; Joubert Fayette; Jamie Burrow (EDIS, 2018)
This is a brochure about the southwest Florida plant clinic. This 2-page document is a minor revison written by Pamela Roberts, Shea Teems, Ramdas Kanissery, Katherine Hendricks, Joubert Fayette, and Jamie Burrow, and published by the Plant Pathology Department, June 2018.